Implementasi Peraturan Daerah Kota Semarang Nomor 4 Tahun 2013 tentang Penanggulangan HIV dan AIDS - Putri, Ignatia Bellatrix Ariesta Parameswari; Nurcahyanto, Herbasuki; Marom, Aufarul (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
HIV and AIDS policy in Semarang City is the government's efforts to tackle the disease HIV and AIDS in the city of Semarang. Semarang as the capital of Central Java province ranks first with a high case-finding, so the Government of Semarang City makes regulation number 4 of 2013 on HIV and AIDS. HIV and AIDS management efforts consisting of four activities there are promotion, prevention, treatment and social rehabilitation. This study aims to describe the process of implementing HIV and AIDS policy conducted by the City of Semarang and to describe the factors that influence policy implementation. This study is an observational study is qualitative descriptive data. Data was collected through in-depth interviews with key informants, the Secretary of the National AIDS Commission (KPA) Semarang, Staff PM Social Services, Youth and Sports of Semarang, Staff P2P Semarang City Health Department, the Village Head Peterongan, People Living with HIV and AIDS, Midwives, Field Coordinator NGO Griya Asa PKBI Semarang, and Chairman of the NGO Griya Asa PKBI Semarang. The results of this study is on the implementation of policies on HIV and AIDS in the city of Semarang is successful because it is considered to be effective in solving problems related to the spread of HIV and AIDS. It is seen from the aspect of precision implementation has been carried out, although not 100 percent. There is a shortage in the factors that affect implementation such as resource and environmental conditions. Based on these conclusions, the researchers recommend to KPA Semarang to improve the indicator still unwell so that the policy response to HIV and AIDS in Semarang can run optimally.